Simulated larval feeding damage patterns of Heliothis armigera(Hübner) and H. punctigera(Wallengren) (Lepidoptera: Noctuidae) on cotton in Australia - Hassan, S.T.S.; Wilson, L.T. (Taylor & Francis, 1993)
Damage by Heliothis armigera (Hübner) and H. punctigera (Wallengren) was simulated by incorporating into a fruit predation model, the effects of host (structure) preference, larval and fruit age‐specific consumption rates, fruit (age class) availability, and seasonal larvae age class availability. The two species showed similar patterns of damage. Differences emerged when fruit and instars were separated by age class. The first‐, fourth‐and fifth‐instar H. armigera larvae damaged more fruiting structures than respective stages of H. punctigera and conversely for other instars. Larvae of H. armigera damaged a greater number of older structures, while those of H. punctigera generally preferred and damaged more younger structures. Numbers of fruiting structures damaged, especially small and medium squares, decreased throughout the season and only increased with cotton regrowth at the end of the season. Damage to large squares occurred throughout the season. Flower damage fluctuated. For small, medium and large bolls, damage increased, and then decreased late in the season. For both species the proportion of bolls representing the larval diet increased with larval age and as the season progressed. The relative control threshold values of H. armigera were obtained by dividing the product of the number of fruiting structures damaged by this species and their mean scalar age, by the corresponding product for H. punctigera. The relative threshold for each species is hence the inverse of the other. The relative control threshold for H. armigera decreases with time, whereas the reverse trend was thus obtained for H. punctigera. These trends indicate the increasing (with time) need to control H. armigera populations more than that of H. punctigera to better protect the fruiting structures during peak squaring and early boll maturation periods. Such differences should be incorporated into an integrated pest management programme for the two species.